STUDI PENDAHULUAN PENGEMBANGAN E-MODUL AJAR GEOGRAFI PADA KURIKULUM MERDEKA PROGRAM SEKOLAH PENGGERAK KELAS X SMA DI KOTA PADANG - Pangaribuan, Dewi Shinta; Ernawati, Ernawati (DEPARTEMEN GEOGRAFI FIS UNP, 2025)
The research aims to (1) obtain information about the use of class X geography teaching modules as a learning resource for students in the independent curriculum of the driving school program, (2) obtain information about educators' responses to the feasibility of e-modules for teaching geography class X school program driving the independent curriculum. This type of research is a preliminary study or Preliminary Research stage on the Plomp development model. Data collection was done by interviews, questionnaires and documentation. Research instruments in the form of questionnaires to educators and students, the processing of research questionnaire data is carried out with descriptive statistical data analysis techniques. The results showed that First, the use of geography teaching modules by educators with an average score of 59.47 was in the sufficient category, and the use of geography teaching modules by students with an average score of 58.21 with sufficient categories. Second, the educator's response to the eligibility of the class X geography teaching module with an average score of 77.7 is in the strong category. With the results of this preliminary study research, the research can be continued on e-module development research to produce development products in the form of class X geography teaching e-modules.